(untitled) (Proceedings of Southern Federal University. Philology, 2026)
10.18522/1995-0640-2026-1-169-177 The study of the possibility of increasing the efficiency of foreign language teaching by improving teaching aids is the aim of this research. The switch of the leading type of activity and the transition of interests into the framework of the educational process, where both cognitive abilities and personality development are formed, is a distinctive feature of adolescence. The teacher’s task is to find teaching tools that will allow students to become active and interested participants in the educational process, and will help maintain interest in learning and the desire for self-development. One of such means, in our view, is gamification, which is built not on replacing serious activities with games, but on accompanying the educational process with elements of gaming activities, which is the relevance of this study. The scientific novelty lies in the theoretical substantiation of the possibility and feasibility of using elements of strategic gamification at the middle stage of training. The practical significance is determined by the need for their use, confirmed by a survey of teachers, an analysis of teaching and methodological complexes in English for grades 7 and the results of experimental training conducted on the basis of the methodological recommendations developed by the author. Key words: gaming activity, strategic gamification, adolescence, elements of gamification